Physicochemical analysis of ham from entire male pigs raised with different feeding and housing conditions - Pereira Pinto, Ricardo (2019)
This study aims to investigate the effect of feeding and housing conditions on physicochemical characteristics of cooked hams produced with meat from entire male pigs. Meat from boars raised under different conditions of housing and feeding (two housing conditions and three levels of inulin added to feed) was used to produce six batches of cooked hams following a standard manufacturing process. Texture profile analysis (hardness, cohesiveness, and chewiness), color analysis, pH, and moisture content were determined. ANOVA and principal component analysis were carried out. Results showed that 6% of inulin added to feed led to significantly lower values of hardness and chewiness. Improved housing conditions hams presented lower pH values. Except for a* parameter (red color), no significant interactions between the two categorical variables, housing and diet, were found. Housing conditions and inulin feeding may have affected meat characteristics; therefore, adjustments of current cooked ham processing parameters might be necessary.